Progressive renal insufficiency related to ALK inhibitor, alectinib. Issue 4 (25th April 2018) - Nagai, Kojiro; Ono, Hiroyuki; Matsuura, Motokazu; Hann, Michael; Ueda, Sayo; Yoshimoto, Sakiya; Tamaki, Masanori; Murakami, Taichi; Abe, Hideharu; Ishikura, Hisashi; Doi, Toshio
Abstract: Alectinib is a second generation anaplastic lymphoma kinase (ALK) tyrosine kinase inhibitor and is generally effective and tolerated in patients who have demonstrated disease progression or adverse effects while on the first generation inhibitor, crizotinib. ALK inhibitors can cause a reversible chronic increase of serum creatinine concentration; however, they rarely induce progressive renal insufficiency. We herein report a case of a 68-year-old woman diagnosed with ALK-positive advanced non-small cell lung cancer and who received ALK inhibitors. Due to dysgeusia and transaminitis, her medication was switched from crizotinib to alectinib. Rapid progressive glomerulonephritis developed 1 year after the initiation of alectinib treatment. A renal biopsy revealed unique kidney lesions in both tubules and glomeruli. Glucocorticoid therapy partially reversed kidney impairment. However, re-administration of alectinib caused kidney dysfunction, which was improved by the cessation of alectinib. Our case suggests that much attention should be paid to kidney function when using ALK inhibitors.